Discussion: Signaling, Information Content, and the Reluctance to Cut Dividends - Senbet, Lemma W. (Journal of Financial and Quantitative Analysis, 1980)
Lemma W. Senbet, Discussion: Signaling, Information Content, and the Reluctance to Cut Dividends, The Journal of Financial and Quantitative Analysis, Vol. 15, No. 4, Proceedings of 15th Annual Conference of the Western Finance Association, June 19-21, 1980, San Diego, California (Nov., 1980), pp. 871-873